Islamic Corporate Governance, Maqashid Syariah Index, Capital Structure, Firm Size, and Firm Value: An Empirical Analysis - Cahya, Bayu Tri; Ulya, Vina Himatul; Ali, Nor Aishah Mohd; Lubis, Irma Suryani; Restuti, Dwi Putri (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2024)
This research investigates the relationship between Islamic corporate governance, the Maghasid Syariah Index, and capital structure on firm value with firm size as a moderating variable. This research uses a quantitative approach, namely secondary data from the company's annual report. The sample used in this research was 41 Sharia Commercial Bank companies registered with the OJK during 2019-2022, according to the sample selection criteria using purposive sampling. The analytical methods used are multiple linear regression analysis and moderated regression analysis. The study results show that Islamic corporate governance and capital structure have a positive and significant effect on firm value, while the Maghasıd Syariah Index does not affect firm value. The study results after the moderating variable show that firm size cannot moderate the Islamic Corporate Governance and Maghasıd Syariah Index on Firm value. Meanwhile, firm size can strengthen the relationship between capital structure and firm value.